Legal Gaps in the Definition of Space Debris - S. S. Popova (Московский журнал международного права)
INTRODUCTION. The article is devoted to the problem of defining the concept of "space debris" from the point of view of two concepts: the concept of safety and the concept of property. The aim of the article is to substantiate the importance of developing a unified definition of space debris and to formulate proposals for eliminating legal gaps in the definition of space debris. The research is based on publications by Russian and foreign specialists in space law, the 1967 Outer Space Treaty, the Committee on the Peaceful Uses of Outer Space Guidelines on Space Debris Mitigation, space debris reduction standards, Russian and US legislation regulating space activities, and draft regulations aimed at ensuring the safety of space activities and space debris reduction. The following methods were employed in the preparation of the article: the comparative analysis method, the analogy method, the logical method, the description method, the generalisation method, and the comparative legal method.RESULTS. The research conducted has enabled the identification of discrepancies in the definition of the concept of 'space debris' from the perspectives of security and property; it is posited that the absence of a consolidated understanding of space debris in the near future may result in deleterious consequences. It is concluded that the precise definition of the concept of space debris is not critical for ensuring the safety of space activities; however, the concept of property requires clarification of space debris criteria in order to realise the possibility of cleaning the near-Earth space and the surface of celestial bodies from anthropogenic pollution. It is proposed that the definition of space debris be formulated within the context of the property concept.DISCUSSION AND CONCLUSIONS. The analysis demonstrates the relevance of the chosen topic, and the discussion of the problems is carried out in the UN Committee on the Peaceful Uses of Outer Space, on other international and national platforms. Despite the efforts of the scientific community, a consensus remains elusive regarding a universally accepted definition of 'space debris'. National jurisdictions make attempts to formulate their own definition of ‘space debris’ in order to allow their residents to carry out new types of space activities, occupying the relevant sectors of the space economy. The paper distinguishes approaches to defining the concept of 'space debris' through the prism of security and property concepts, and formulates proposals for formalizing the concept of 'space debris' from the perspective of the property concept.